212 CLEC-1 is a novel myeloid immune checkpoint for cancer immunotherapy limiting tumor cells phagocytosis and synergizing with tumor-targeted antibodies. (9th November 2020) - Gauttier, Vanessa; Drouin, Marion; Pengam, Sabrina; Saenz, Javier; Evrard, Bérangère; Mary, Caroline; Teppaz, Géraldine; Desselle, Ariane; Thépénier, Virginie; Wilhelm, Emmanuelle; Chiffoleau, Elise; Poirier, Nicolas
Abstract : Background: Myeloid cells represent one of the most abundant immune cell types in solid tumors that impede myeloid phagocytosis by triggering 'don't eat me' and 'don't find me' signals. Recent literature demonstrates that C-type lectin receptors (CLRs) normally constrain immune cell–mediated tissue damage by suppressing myeloid cell activation and then promote tumor immune evasion. We previously identified the orphan (CLRs) CLEC-1 as over-expressed in situation of established immune tolerance and reported that CLEC-1 expression by dendritic cells (DCs) and macrophages is enhanced by TGFβ and tempers downstream T cells responses. Furthermore, we reported that CLEC-1 is highly expressed by myeloid cells purified from human tumor micro-environment significantly more expressed by suppressive macrophages. Methods: As DCs and macrophages are professional phagocytes of dying/dead cell, we evaluated whether CLEC-1 could be a receptor of damaged cells in the phagocytosis. Results: We found that CLEC-1 fusion protein, binds specifically to late apoptotic and secondary necrotic healthy or tumor cells induced by chemotherapy, radiation (UV, X-ray) or culture stress conditions. Importantly, we observed in vivo that CLEC-1 deficient mice, but not wild-type, eradicate MC38 colorectal tumors in combination with cytotoxic and immunogenic chemotherapy (eg. Cyclophosphamide. We then generated, screened and identified different anti-human Clec-1 antagonist monoclonal antibodies (mAbs) with the capacity to block the CLEC-1/CLEC-1L interaction. We discovered that various antagonist CLEC-1 mAbs, but not non-antagonist CLEC-1 control mAbs, increase the phagocytosis of CLEC-1L-positive human tumor cells by human CLEC-1 expressing TGFβ-polarized DCs or macrophages. Indeed, TGFβ-polarized DCs phagocytosed more efficiently Rituximab (anti-CD20 mAb)-opsonized Burkitt lymphoma cells (Raji) as well as bare NSCLC cells (A549) when CLEC-1 is antagonized by antibodies. Furthermore, macrophages more productively engulfed Rituximab-opsonized Raji cells as well in the context of CLEC-1 blockade (2–3 fold increase). Moreover, Cetuximab opsonized colon carcinoma cells (DLD-1; EGFR+) and Trastuzumab opsonized mammary carcinoma cells (SK-BR-3; Her2+) were likewise more phagocytosed by CLEC-1 blocked macrophages. Conclusions: Altogether, these data indicate illustrate that CLEC-1 broadly inhibits tumor-cell phagocytosis and synergized with tumor-targeted cytotoxic monoclonal antibodies in both solid and hematological tumors.